Aprūpes principi gerontoloģiskā profila pacientiem ar Alcheimera slimību - Prosorovska, Valērija (Latvijas Universitāte, 2025)
Bakalaura darbā “Aprūpes principi gerontoloģiskā profila pacientiem ar Alcheimera slimību” tiek pētīti un analizēti Alcheimera slimības gerontoloģisko pacientu aprūpes principi, īpaši Latvijas sociālās aprūpes iestādēs. Alcheimera slimība ir viena no izplatītākajām demences formām, kas ievērojami ietekmē pacienta kognitīvās spējas un ikdienas gaitas, pieprasot specializētu un profesionālu aprūpi. Demogrāfisko tendenču dēļ šīs problēmas aktualitāte pieaug, jo sabiedrības novecošanās palielina nepieciešamību pēc uzlabojumiem gerontoloģiskā aprūpē. Darba mērķis ir izpētīt un analizēt aprūpes principus gerontoloģiskā profila pacientiem ar Alcheimera slimību, identificējot esošos principus, to efektivitāti un iespējamos uzlabojumus, lai veicinātu pacientu dzīves kvalitātes uzlabošanu un aprūpes personāla darba efektivitāti. Pētījuma jautājums: Kādi ir aprūpes principi gerontoloģiskā profila pacientiem ar Alcheimera slimību? Pētījums tika īstenots, pielietojot kvalitatīvas izpētes metodi – daļēji strukturētas intervijas ar 16 jautājumiem. Kopumā tika intervētas 10 vispārējās aprūpes māsas. No tām 5 strādā sociālās aprūpes centrā «A» un 5- sociālās aprūpes centrā «B». Respondenti ikdienā sniedz aprūpi pacientiem ar Alcheimera slimību. Atslēgvārdi: Alcheimera slimība, individualizēta aprūpe, sociālās aprūpes centrs, demences pacienti, aprūpes principi.

The bachelor's thesis "Care Principles for Geriatric Patients with Alzheimer's Disease" examines and analyzes the care principles for geriatric patients with Alzheimer's disease, particularly in Latvian social care institutions. Alzheimer's disease is one of the most common forms of dementia, significantly affecting the patient's cognitive abilities and daily functioning, thus requiring specialized and professional care. Due to demographic trends, the relevance of this issue is increasing as the aging population raises the need for improved gerontological care. The aim of the study is to explore and analyze the care principles for geriatric patients with Alzheimer's disease, identifying existing principles, their effectiveness, and potential improvements to enhance the quality of life for patients and the efficiency of care staff. Research question: What are the care principles for geriatric patients with Alzheimer's disease? The study was conducted using a qualitative research method – semi-structured interviews with 16 questions. A total of 10 general care nurses were interviewed, of which 5 work at the social care center «A» and 5 at the social care center «B». The respondents provide daily care for patients with Alzheimer's disease. Keywords: Alzheimer's disease, individualized care, social care center, dementia patients, care principles. Atslēgvārdi: Alcheimera slimība, individualizēta aprūpe, sociālās aprūpes centrs, demences pacienti, aprūpes principi. The bachelor's thesis "Care Principles for Geriatric Patients with Alzheimer's Disease" examines and analyzes the care principles for geriatric patients with Alzheimer's disease, particularly in Latvian social care institutions. Alzheimer's disease is one of the most common forms of dementia, significantly affecting the patient's cognitive abilities and daily functioning, thus requiring specialized and professional care. Due to demographic trends, the relevance of this issue is increasing as the aging population raises the need for improved gerontological care. The aim of the study is to explore and analyze the care principles for geriatric patients with Alzheimer's disease, identifying existing principles, their effectiveness, and potential improvements to enhance the quality of life for patients and the efficiency of care staff. Research question: What are the care principles for geriatric patients with Alzheimer's disease? The study was conducted using a qualitative research method – semi-structured interviews with 16 questions. A total of 10 general care nurses were interviewed, of which 5 work at the social care center «A» and 5 at the social care center «B». The respondents provide daily care for patients with Alzheimer's disease. Keywords: Alzheimer's disease, individualized care, social care center, dementia patients, care principles.
Care Principles for Geriatric Patients with Alzheimer's Disease
Keywords: Veselības un sporta zinātnes; Alcheimera slimība; Individualizēta aprūpe; Sociālās aprūpes centrs; Aprūpes principi